2020
DOI: 10.1038/s41598-020-74698-2
|View full text |Cite
|
Sign up to set email alerts
|

Tracking elemental changes in an ischemic stroke model with X-ray fluorescence imaging

Abstract: Stroke is a leading cause of long-term disability in adults and a leading cause of death in developed nations. The cascade of cellular events and signalling that occur after cerebral ischemia are complex, however, analyzing global element markers of metabolic state affords the means to monitor stroke severity, status of injury, and recovery. These markers provide a multi-parameter method for assessing changes through the post-stroke time course. We employ synchrotron-based elemental mapping to follow elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
4
15
0
2
Order By: Relevance
“…3 A and summarized in Table S3 ). Additional metabolites, such as lactate, glutamate, ATP+ADP, aggregated protein content, S, Cl, K, and Zn also followed this general trend of deviations from normal levels through the penumbra and continuing into the infarct core, but not all reach statistically significant changes at 24-hours post-stroke ( Pushie et al, 2020 ). Nevertheless, the infarct and penumbra ROIs generally demonstrated the same trends in metabolite concentrations across all 3 animal groups ( Table S3 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…3 A and summarized in Table S3 ). Additional metabolites, such as lactate, glutamate, ATP+ADP, aggregated protein content, S, Cl, K, and Zn also followed this general trend of deviations from normal levels through the penumbra and continuing into the infarct core, but not all reach statistically significant changes at 24-hours post-stroke ( Pushie et al, 2020 ). Nevertheless, the infarct and penumbra ROIs generally demonstrated the same trends in metabolite concentrations across all 3 animal groups ( Table S3 ).…”
Section: Resultsmentioning
confidence: 93%
“…Glycogen was increased nearly 1.4 x in the female post-stroke penumbra compared to levels in the penumbra of post-stroke males. At 24-hours post-stroke, the glial response following ischemia peaks resulting in astrocyte activity and glial scar formation ( Pushie et al, 2020 , Hackett et al, 2016 ). Sex differences have been reported in astrocyte estrogen receptors in the hippocampus leading to an increase in glycogen metabolism ( Ibrahim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From ref. 29, using this collimator results in dose peaks with full width at half maximum (FWHM) of 1.0 mm at isocenter. The FWHM is relevant because megavoltage mini beams take a profile with a sharp peak widening towards the base, as opposed to synchrotron beams which are quasi-parallel.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades it has indeed been established that certain neurodegenerative diseases are associated with the dyshomeostasis of essential metals, such as Fe, Cu and Zn [ 23 ], which are present in gray matter at concentrations between 0.1–0.5 mM [ 24 , 25 ]. Several studies have demonstrated that these metal ions are directly implicated in the pathophysiology and pathogenesis of Alzheimer’s disease [ 26 28 ], multiple sclerosis (MS) [ 29 – 31 ] and stroke [ 32 ]. To evaluate the potential that the quantification of plasma metalloproteins may offer in terms of disease diagnosis, progression, or severity, we conducted a pilot study in which we quantified Fe, Cu and Zn-containing metalloproteins in plasma collected from AIS and MS participants (disease control) as well as healthy controls.…”
Section: Introductionmentioning
confidence: 99%